An unusual pelvic mass: Contrast‐enhanced sonographic diagnosis of pelvic splenosis. Issue 3 (16th November 2018) - Kruger, Ross; Freeman, Simon
Abstract: Splenosis is an unusual condition representing auto‐transplantation of splenic tissue following splenic trauma or surgery. When detected on imaging studies, the splenosis deposits are usually misinterpreted as pathological masses. We present a case where a pelvic mass incidentally visualized on an MRI examination, was proven to represent a deposit of splenosis by contrast enhanced ultrasound (CEUS). CEUS demonstrated persistent late‐phase enhancement characteristic of splenic tissue. Ultrasound practitioners should be aware of this condition when an unusual abdominal or pelvic mass is encountered in a patient with a history of splenic trauma or surgery. CEUS is ideally suited to confirming the diagnosis.